2019
DOI: 10.1038/s41593-019-0498-9
|View full text |Cite
|
Sign up to set email alerts
|

FUS-mediated regulation of acetylcholine receptor transcription at neuromuscular junctions is compromised in amyotrophic lateral sclerosis

Abstract: Users may view, print, copy, and download text and data-mine the content in such documents, for the purposes of academic research, subject always to the full Conditions of use:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
114
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(118 citation statements)
references
References 46 publications
3
114
1
Order By: Relevance
“…Finally, in motor neuron/myotube co-cultures, ALS-mutant FUS was intrinsically toxic to both motor neurons and myotubes. Altogether, these data show that FUS plays a key role in regulating selective expression of AChR genes in subsynaptic nuclei and indicate that intrinsic toxicity of ALS-mutant FUS in the muscle may be critical for ALS [115]. FUS is also involved in SMA, through a direct interaction between FUS and SMN through the U1-snRNP.…”
Section: Fusmentioning
confidence: 70%
See 1 more Smart Citation
“…Finally, in motor neuron/myotube co-cultures, ALS-mutant FUS was intrinsically toxic to both motor neurons and myotubes. Altogether, these data show that FUS plays a key role in regulating selective expression of AChR genes in subsynaptic nuclei and indicate that intrinsic toxicity of ALS-mutant FUS in the muscle may be critical for ALS [115]. FUS is also involved in SMA, through a direct interaction between FUS and SMN through the U1-snRNP.…”
Section: Fusmentioning
confidence: 70%
“…FUS also exerts critical roles in neuromuscular junction development. Animal models of FUS-ALS show alteration of synaptic transmission and modification of NMJ numbers and size [110][111][112][113][114], and we recently demonstrated that FUS is required for the post-synaptic development of the NMJ [115]. Indeed, both knock-in and knock-out mice for Fus developed NMJ morphology defects.…”
Section: Fusmentioning
confidence: 99%
“…Furthermore, the replacement of murine FUS with a mutated human form activates an integrated stress response and inhibit local intra-axonal protein synthesis in hippocampal neurons and sciatic nerves, resulting in synaptic dysfunction (López-Erauskin et al, 2018). A recent study found that transcription of an acetylcholine receptor is compromised in FUS-mediated ALS, thus supporting the idea that FUS affects gene expression (Picchiarelli et al, 2019).…”
Section: Discussionmentioning
confidence: 62%
“…On the other hand, selective reduction of mutant SOD1 expression in skeletal muscle of mutant SOD1 transgenic mice did not affect their disease course, neither did increasing muscle fiber number and diameter by follistatin expression [27,28]. Intriguingly, a recent study reported that ALS-mutant FUS is intrinsically toxic to both motor neurons and muscle cells, and toxicity in muscle may be attributable to defective FUS-mediated transcriptional regulation of acetylcholine receptor subunit genes [29]. While this and other studies in FUS-ALS mouse models indicate that a gain-of-toxic-function of ALS-mutant FUS is required to cause motor neuron degeneration [30][31][32] Interestingly, FGF signaling has previously been implicated in ALS pathogenesis, through retrograde FGF signaling from muscle to motor neuron [33].…”
Section: Discussionmentioning
confidence: 95%